3217 Catatonia, Delirium and Coma: Implications for Mortality - Wilson, Jo Ellen (J Clin Transl Sci, 2019)
OBJECTIVES/SPECIFIC AIMS: Delirium, a form of acute brain dysfunction, characterized by changes in attention and alertness, is a known independent predictor of mortality in the Intensive Care Unit (ICU). We sought to understand whether catatonia, a more recently recognized form of acute brain dysfunction, is associated with increased 30-day mortality in critically ill older adults. METHODS/STUDY POPULATION: We prospectively enrolled critically ill patients at a single institution who were on a ventilator or in shock and evaluated them daily for delirium using the Confusion Assessment for the ICU and for catatonia using the Bush Francis Catatonia Rating Scale. Coma, was defined as a Richmond Agitation Scale score of −4 or −5. We used the Cox Proportional Hazards model predicting 30-day mortality after adjusting for delirium, coma and catatonia status. RESULTS/ANTICIPATED RESULTS: We enrolled 335 medical, surgical or trauma critically ill patients with 1103 matched delirium and catatonia assessments. Median age was 58 years (IQR: 48 - 67). Main indications for admission to the ICU included: airway disease or protection (32%; N=100) or sepsis and/or shock (25%; N=79. In the unadjusted analysis, regardless of the presence of catatonia, non-delirious individuals have the highest median survival times, while delirious patients have the lowest median survival time. Comparing the absence and presence of catatonia, the presence of catatonia worsens survival (Figure 1). In a time-dependent Cox model, comparing non-delirious individuals, holding catatonia status constant, delirious individuals have 1.72 times the hazards of death (IQR: 1.321, 2.231) while those with coma have 5.48 times the hazards of death (IQR: 4.298, 6.984). For DSM-5 catatonia scores, a 1-unit increase in the score is associated with 1.18 times the hazards of in-hospital mortality. Comparing two individuals with the same delirium status, an individual with a DSM-5 catatonia score of 0 (no catatonia) will have 1.178 times the hazard of death (IQR: 1.086, 1.278), while an individual with a score of 3 catatonia items (catatonia) present will have 1.63 times the hazard of death. DISCUSSION/SIGNIFICANCE OF IMPACT: Non-delirious individuals have the highest median survival times, while those who are comatose have the lowest median survival times after a critical illness, holding catatonia status constant. Comparing the absence and presence of catatonia, the presence of catatonia seems to worsen survival. Those individual who are both comatose and catatonic have the lowest median survival time.